Efektivitas Latihan Relaksasi Autogenik terhadap Intensitas Nyeri pada Pasien Pascaoperasi Fraktur (Journal of Telenursing (JOTING), 2023)
This study aims to identify the effectiveness of autogenic relaxation exercises on pain intensity in post-operative fracture patients at Advent, Royal Prima, and Murni Teguh Medan Hospitals. This research method is a quasi-experiment with a non-equivalent control group design. Sampling used non-probability sampling with the convenience sampling method. The respondents in this study were 24-hour post-surgical fracture patients who were hospitalized, totaling 78 respondents consisting of 39 respondents in the intervention group and 39 respondents in the control group. Data analysis used Mann-Whitney statistical test analysis. The results showed that p-value = 0.000 (p